Diagnostics and classification of muscle injuries in sports - Tscholl. P.; Meynard, T.; Le Than, N.; Neroladaki, A. (Swiss Sports & Exercise Medicine, 2018)
Muscle injuries are responsible for up to one third of the musculoskeletal injuries occuring in professional football and summer Olympic Games. Classifying injuries has the objective to define the extent, to predict the time-loss, and potentially to suggest a treatment plan to optimize the return to sport and prevent from re-injury. Most recent classification systems have integrated patient`s history, clinical examination, and diagnostic imaging, to describe severity and therefore time-loss. The different aspects and the most frequently used classification systems are discussed with special regard their validity to predict return to sport. Abstract from author